Gamification: Saving in Digital Banking is Like Playing A Game - Rimenda, Tetty; Aulia, Meidina Rosa; Listiawati, Rodiana; Marbun, Jhonny (UI Scholars Hub, 2022)
Manuscript type: Research Paper Research Aims: The purpose of this paper is to explore the effect of gamification, such as badges, elements and challenges that are applied to banking features, on customers' intention to save Design/methodology/approach: This research explores how gamification is applied in digital banking. The study was conducted to test the effect of using the principles of badges, levels and challenges applied to savings can motivate millennials to save. Respondents are XYZ digital bank customers who were born between 1980 -2000. Data from 172 samples were analysed using partial least squares structural equation modelling, Research Findings: The results showed that gamification used in banking positively affects consumer decisions to save. Badge-element strongly predicts how gamification is perceived as motivation in saving activities. The results also show that levels-elements affect the customer's willingness to save, while the challenge element affects the least interest in saving. Theoretical Contribution/Originality: Research on the use of technology in the banking sector can contribute to banking facing intense competition. Further research is needed to explore gamification to improve young consumers' financial well-being and good saving behaviour. Practitioner/Policy Implication: The research supports the use of gamification in the banking sector because gamification can encourage young customers to save money. Research limitation/Implications: Even though gamification is a trending topic, its use in the banking sector must adhere to prudence principles.